2014
DOI: 10.1038/srep06158
|View full text |Cite
|
Sign up to set email alerts
|

DNA G-segment bending is not the sole determinant of topology simplification by type II DNA topoisomerases

Abstract: DNA topoisomerases control the topology of DNA. Type II topoisomerases exhibit topology simplification, whereby products of their reactions are simplified beyond that expected based on thermodynamic equilibrium. The molecular basis for this process is unknown, although DNA bending has been implicated. To investigate the role of bending in topology simplification, the DNA bend angles of four enzymes of different types (IIA and IIB) were measured using atomic force microscopy (AFM). The enzymes tested were Esche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
(109 reference statements)
2
18
0
Order By: Relevance
“…Two of the models, the Gsegment DNA-bending model (Vologodskii et al 2001) and the hooked-juxtaposition model (Buck and Zechiedrich 2004), propose that local geometry, such as bending by the topoisomerase or selection of Bhooked^conformations in juxtaposed DNA segments, results in preferential activity on linked DNA segments which, coupled with the ATPdependent unidirectional strand passage, results in global simplification of DNA topology. Structural studies and direct mechanical measurements have revealed that Topo IIA bend DNA upon binding (Dong and Berger 2007;Hardin et al 2011;Lee et al 2012Lee et al , 2013Thomson et al 2014) and thus that this enzyme likely has a higher binding affinity for bent DNA, such as at the apices of plectonemes in supercoiled DNA. To date, however, the proposed models cannot fully explain the below-equilibrium simplification phenomenon, indicating that the models may only partially reflect the mechanistic basis of this intriguing effect (Hardin et al 2011;Liu et al 2010;Martínez-García et al 2014;Seol et al 2013b;Thomson et al 2014;Yan et al 1999).…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the models, the Gsegment DNA-bending model (Vologodskii et al 2001) and the hooked-juxtaposition model (Buck and Zechiedrich 2004), propose that local geometry, such as bending by the topoisomerase or selection of Bhooked^conformations in juxtaposed DNA segments, results in preferential activity on linked DNA segments which, coupled with the ATPdependent unidirectional strand passage, results in global simplification of DNA topology. Structural studies and direct mechanical measurements have revealed that Topo IIA bend DNA upon binding (Dong and Berger 2007;Hardin et al 2011;Lee et al 2012Lee et al , 2013Thomson et al 2014) and thus that this enzyme likely has a higher binding affinity for bent DNA, such as at the apices of plectonemes in supercoiled DNA. To date, however, the proposed models cannot fully explain the below-equilibrium simplification phenomenon, indicating that the models may only partially reflect the mechanistic basis of this intriguing effect (Hardin et al 2011;Liu et al 2010;Martínez-García et al 2014;Seol et al 2013b;Thomson et al 2014;Yan et al 1999).…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
“…Structural studies and direct mechanical measurements have revealed that Topo IIA bend DNA upon binding (Dong and Berger 2007;Hardin et al 2011;Lee et al 2012Lee et al , 2013Thomson et al 2014) and thus that this enzyme likely has a higher binding affinity for bent DNA, such as at the apices of plectonemes in supercoiled DNA. To date, however, the proposed models cannot fully explain the below-equilibrium simplification phenomenon, indicating that the models may only partially reflect the mechanistic basis of this intriguing effect (Hardin et al 2011;Liu et al 2010;Martínez-García et al 2014;Seol et al 2013b;Thomson et al 2014;Yan et al 1999). Recently, it was demonstrated that the binding affinity of Topo IV is linearly related to the linking number for negatively supercoiled plasmid DNA (Litwin et al 2015), which is consistent with previous observations of Topo IIA binding to DNA crossovers (Zechiedrich and Osheroff 1990).…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
“…4) on the plasmid DNAs. Researchers have used persistence length [17], curvature [30] and bending angle [31] to represent the geometric feature of linear DNAs. Particularly, persistence length has been widely used to characterize the flexible mechanics of linear DNAs [32][33][34].…”
Section: Afm Imagingmentioning
confidence: 99%
“…Two of the models, the G-segment DNA-bending model (Vologodskii et al 2001) and the hooked-juxtaposition model (Buck and Zechiedrich 2004), propose that local geometry such as bending by the topoisomerase, or selection of “hooked” conformations in juxtaposed DNA segments, results in preferential activity on linked DNA segments, which, coupled with the ATP-dependent unidirectional strand passage, results in global simplification of DNA topology. Structural studies and direct mechanical measurements have revealed that Topo IIA enzymes bend DNA upon binding (Dong and Berger 2007; Hardin et al 2011; Lee et al 2013; Lee et al 2012; Thomson et al 2014), thus Topo IIA likely has a higher binding affinity for bent DNA such as at the apices of plectonemes in supercoiled DNA. To date, however, the proposed models cannot fully explain the below-equilibrium simplification phenomenon, indicating that the models may only partially reflect the mechanistic basis of this intriguing effect (Hardin et al 2011; Liu et al 2010; Martínez-García et al 2014; Seol et al 2013b; Thomson et al 2014; Yan et al 1999).…”
Section: Dna Writhe Dependent Protein Activitymentioning
confidence: 99%
“…Structural studies and direct mechanical measurements have revealed that Topo IIA enzymes bend DNA upon binding (Dong and Berger 2007; Hardin et al 2011; Lee et al 2013; Lee et al 2012; Thomson et al 2014), thus Topo IIA likely has a higher binding affinity for bent DNA such as at the apices of plectonemes in supercoiled DNA. To date, however, the proposed models cannot fully explain the below-equilibrium simplification phenomenon, indicating that the models may only partially reflect the mechanistic basis of this intriguing effect (Hardin et al 2011; Liu et al 2010; Martínez-García et al 2014; Seol et al 2013b; Thomson et al 2014; Yan et al 1999). Recently, it was demonstrated that Topo IV binding affinity is linearly related to linking number for negatively supercoiled plasmid DNA (Litwin et al 2015), consistent with previous observations of Topo IIA binding to DNA crossovers (Zechiedrich and Osheroff 1990).…”
Section: Dna Writhe Dependent Protein Activitymentioning
confidence: 99%